Pengembangan Desain Pengalaman Pengguna Sistem Monitoring Pendaki Gunung Berbasis GPS dan LoRA dengan Metode Agile Scrum - Aditya Aji Pamungkas; Muhammad Rafli Krishnadanu Putra Wardana; Agung Dwi Oktavian; Dicky Febri Primadani; Dia Naufal Abiyyu Tsaqif; Sholiq sholiq (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2024)
Indonesia is home to approximately 400 mountains that attract climbers, both local and international. The increasing number of climbers each year correlates with a rise in accidents. According to data from the National Search and Rescue Agency (BASARNAS), climbing accidents have increased over the past four years. In 2018 alone, there were 23 incidents resulting in 6 fatalities, 4 climbers reported missing, 7 climbers fell ill, and 592 climbers were rescued. Human error, such as choosing the wrong route and adverse weather conditions, remains the primary cause of climbers getting lost. To address these challenges, this research develops a GPS and Long Range (LoRa) based mountain climber monitoring system. The system utilizes GPS to track climbers' locations, heart rate sensors to monitor health conditions, and a buzzer for early warnings when climbers enter restricted areas. It also features a panic button for sending SOS signals to rescue posts. Agile Scrum methodology is employed in the system development, enabling iterative and collaborative software development. Research findings indicate that this system enhances efficiency and effectiveness in monitoring and rescuing climbers in distress, thereby improving mountain climbing safety and comfort.